Integrating Space Weather into K-5 STEM education through hands-on learning - Ozturk, Dogacan Su (Frontiers in Astronomy and Space Sciences, 2025)
Space Weather encompasses multiple elements of the Science, Technology, Engineering, and Mathematics (STEM) education standards, offering an optimum context for interdisciplinary learning. Because space is inherently interesting to young learners, it presents a unique opportunity to enhance engagement and curiosity in science. Although Space Weather is not typically included in K–5 curricula due to its perceived conceptual complexity, we developed and implemented a 4-week “Northern Lights” curriculum for grades K-5 to introduce physical components at the elementary level. The course introduced concepts spanning from the Sun to Earth and emphasized connections between physical and Earth sciences. Through hands-on, inquiry-based activities, students demonstrated a strong grasp of fundamental principles and were able to relate their learning to real-world phenomena. This paper presents the design, implementation, and outcomes of these activities, highlighting the potential of Space Weather as an accessible and inspiring framework for early STEM education.